Employee engagement driving program: Efforts to optimize employee performance - Pundani Eki Pratiwi; Siti Nuzulia; Bogy Febriatmoko; Pradipta Christy Pratiwi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
A company that is undergoing a transition period often faces employee work behavior that does not support the achievement of company goals. In this service partner, employees show minimal work behavior, lack of innovation, lack of energy, and lack of initiative. These emerging behaviors illustrate disengagement behavior that affects company performance. This condition makes it difficult for companies to carry out existing business strategies. The company needs a way to increase employee engagement in the process of implementing company strategies that support the achievement of company goals/performance. To overcome these problems, the service team uses the "Employee Engagement Driving Program" as an effort to optimize employee performance. The purpose of this service is to help companies to be able to encourage their employees to have high engagement, so as to improve company performance. There are three methods in this program, namely, engagement training, group coaching, and individual counseling. This service is attended by supervisors who will encourage their team to be more engaged at work and in the company. The result of this program is the supervisor's ability to create goals and action plans to advance his team and correlate with the work behavior shown. Outputs in the service are articles in the mass media, video highlights, and scientific articles.